Assessment of musculoskeletal load in refuse collectors - Zbigniew W. Jóźwiak; Alicja Bortkiewicz; Teresa Makowiec-Dąbrowska; Bronisław Kapitaniak (Nofer Institute of Occupational Medicine, 2013)
Background: The aim of this work was to assess the load on the musculoskeletal system and its effects in the collectors of solid refuse. The rationale behind this study was to formulate proposals how to reduce excessive musculoskeletal load in this group of workers. Material and Methods: The study group comprised 15 refuse collectors aged 25 to 50 years. Data about the workplace characteristics and subjective complaints of workers were collected by the free interview and questionnaire. During the survey the photorecording of the workpostures, the distance and velocity by GPS recorders, measurements of forces necessary to move containers, energy expenditure (lung ventilation method), workload estimation using the Firstbeat system and REBA method and stadiometry were done. Results: The distance walked daily by the collectors operating in terms of 2 to 3 in urban areas was about 15 km, and in rural areas about 18 km. The most frequent musculoskeletal complaints concerned the feet (60% subjects), knees, wrists and shoulders (over 40% subjects). After work-shift all examined workers had vertebral column shorter by 10 to 14 mm (11.4 mm mean). Conclusions: The results of our study show that the refuse collectors are subjected to a very high physical load because of the work organization and the way it is performed. To avoid adverse health effects and overload it is necessary to undertake ergonomic interventions, involving training of workers to improve the way of their job performance, active and passive leisure, technical control of the equipment and refuse containers, as well as the renegotiation of contracts with clients, especially those concerning non-standard containers. Med Pr 2013;64(4):507-519